Closing the Gaps to Understand the Tick Transmission of Anaplasma marginale among Giant Anteaters (Myrmecophaga tridactyla) in Argentina - Guillemi, Eliana Carolina; Imbert, Mélody; De La Fourniere, Sofia; Orozco, Maria Marcela; Peña Martínez, Jorge; Rosas, Ana Carolina; Montenegro, Valeria Noely; Farber, Marisa Diana (MDPI, 2023)
Anaplasma marginale, a well-known cattle pathogen of tropical and subtropical world regions, has been previously molecularly characterized in a giant anteater (Myrmecophaga tridactyla) from Corrientes, Argentina. Ticks or other hematophagous arthropod involved in the wild transmission cycle remained unknown. The aim of the present study was to analyze the simultaneous occurrence of A. marginale in blood samples and ticks from giant anteaters from Corrientes in order to investigate if ticks could be relevant in the transmission among these mammals. Blood samples from 50 giant anteaters collected in different years and 26 ticks Amblyomma dubitatum and A. sculptum were studied through the molecular amplification of two unequivocal species-specific genes from A. marginale: msp5 and msp1β. Twenty five giant anteaters and tick organs (salivary glands, gut and oviduct) from 11 ticks tested positive to the A. marginale DNA amplification. The further molecular characterization through MSP1a tandem repeats analysis revealed the presence of genotypes circulating among giant anteaters that had been previously identified in cattle blood samples from the same geographical region. These results confirm the presence of A. marginale in giant anteaters in Corrientes and suggests that A. dubitatum and A. sculptum ticks could be involved in the transmission among giant anteaters. Future studies will determine the role of these tick species in the wild transmission cycle in the study area and the eventual connection with the domestic cycle.